Muscle mass decline, arterial stiffness, white matter hyperintensity, and cognitive impairment: Japan Shimanami Health Promoting Program study. Issue 4 (29th March 2017) - Kohara, Katsuhiko; Okada, Yoko; Ochi, Masayuki; Ohara, Maya; Nagai, Tokihisa; Tabara, Yasuharu; Igase, Michiya
Abstract: Background: There is a close association between frailty and cognitive impairment. However, the underlying contribution of sarcopenia to the development of cognitive impairment is unclear. We investigated the possible association between muscle mass decline and cognitive impairment in a cross‐sectional study of 1518 subjects aged 55 years or above. We also evaluated arterial stiffness and white matter hyperintensities (WMHs) as possible underlying mechanisms for this association. Methods: Two sarcopenic indices were measured: thigh muscle cross‐sectional area (CSA; calculated by computed tomography) and skeletal muscle mass (bioelectric impedance). Muscle mass decline was defined as either the bottom 10% or 20% of participants for each sex. Cognitive function was assessed using the Touch Panel‐type Dementia Assessment Scale, and brachial–ankle pulse wave velocity was measured as an index of arterial stiffness. Results: Both sarcopenic indices were modestly but significantly associated with brachial–ankle pulse wave velocity in male and female subjects. The presence of WMHs was significantly associated with low thigh muscle CSA in men and with low skeletal muscle mass in women. The Touch Panel‐type Dementia Assessment Scale score was modestly but significantly and positively associated with thigh muscle CSA in men and skeletal muscle mass in women. Muscle mass decline in the bottom 10% of participants on both sarcopenic indices was significantly and independently related to cognitive impairment in women. Conclusions: Lower sarcopenic indices are significantly related to lower cognitive scores. Arterial stiffness and WMHs could account, at least in part, for this association.